Development of ex situ normothermic reperfusion as an innovative method to assess pancreases after preservation. (26th August 2021) - Ogbemudia, Ann Etohan; Hakim, Gabriella; Dengu, Fungai; El‐Gilani, Faysal; Dumbill, Richard; Mulvey, John; Sayal, Karen; Prudhomme, Thomas; Mesnard, Benoit; Rozenberg, Kaithlyn; Lo Faro, Letizia; James, Timothy; et al.
Summary: Static cold storage (SCS) is the standard method for pancreas preservation prior to transplantation; however, it does not permit organ assessment. Normothermic reperfusion (NR) is utilized clinically for other organs to assess viability. Our aim was to develop NR using normothermic machine perfusion technique to simulate reperfusion at the time of transplantation, enabling evaluation of oxygenated hypothermic machine perfusion (HMPO2) as a newer strategy to optimize pancreas preservation. 13 porcine pancreases procured after circulatory death were divided into 3 groups: 4 pancreases preserved using SCS, and 2 groups preserved by HMPO2 ( n = 4 and n = 5, differing by type of preservation solution). Duration of perfusion or cold storage was 6 hours before the 1‐hour assessment using NR. Outcome measures were perfusion characteristics, biochemistry and change in tissue water mass as oedema assessment. During NR, the HMPO2 groups demonstrated better perfusion characteristics, normal macroscopic appearances, decreased water mass and one HMPO2 group demonstrated a response to glucose stimulation. Conversely, the SCS group showed an increased water mass and developed early macroscopic appearances of oedema, interstitial haemorrhage and minimal portal outflow. This study suggests that ex situ assessment of pancreases by NR is promising, and that HMPO2 may be better than SCS. Abstract : In this paper, we describe an efficient method of assessing ex situ pancreas grafts in order to evaluate novel strategies for pancreas preservation. We found that oxygenated hypothermic machine perfusion may prove to be a new and promising direction for pancreas preservation, with the potential to improve organ utilization rates.